Characteristics of Fibres Based on Secondary Raw Materials and Their Use in Concrete Technology - Sedlmajer, Martin; Bubeník, Jan; Zach, Jiří; Novák, Vítězslav (Czech Technical University in Prague, 2024)
Different types of fibres in cementitious composites, particularly in concrete, are currently used for a number of reasons. Fibres are being added to improve mechanical properties (especially steel and glass fibres), to increase the durability – to reduce occurrence of microcracks during the concrete aging (mainly synthetic and cellulose fibres), or to increase the fire resistance (polypropylene fibres). Within the study, characterization of different types of alternative fibres (fibres generated during waste recycling that would otherwise end in incinerators or landfills) with possible use in cementitious composites. These were fibres from recycled PET bottles, paper, and mineral wool, whose properties were compared to the traditionally used cellulose and polypropylene fibres. In the experimental part, the thickness, length, shape, and surface of individual fibres were monitored by an optical microscope. Furthermore, the amount of heat of combustion was determined by the calorimetric method, and the differential thermal analysis (DTA) was carried out for determination of the impact of high temperature on monitored fibres. The microstructure of fibres was monitored using a scanning electron microscope. The focus of the experimental study was on fibres usable in concrete and capable of enduring high temperature stress.

Different types of fibres in cementitious composites, particularly in concrete, are currently used for a number of reasons. Fibres are being added to improve mechanical properties (especially steel and glass fibres), to increase the durability – to reduce occurrence of microcracks during the concrete aging (mainly synthetic and cellulose fibres), or to increase the fire resistance (polypropylene fibres). Within the study, characterization of different types of alternative fibres (fibres generated during waste recycling that would otherwise end in incinerators or landfills) with possible use in cementitious composites. These were fibres from recycled PET bottles, paper, and mineral wool, whose properties were compared to the traditionally used cellulose and polypropylene fibres. In the experimental part, the thickness, length, shape, and surface of individual fibres were monitored by an optical microscope. Furthermore, the amount of heat of combustion was determined by the calorimetric method, and the differential thermal analysis (DTA) was carried out for determination of the impact of high temperature on monitored fibres. The microstructure of fibres was monitored using a scanning electron microscope. The focus of the experimental study was on fibres usable in concrete and capable of enduring high temperature stress.
Characteristics of Fibres Based on Secondary Raw Materials and Their Use in Concrete Technology
Keywords: fibres based on secondary raw materials; recycling; concrete; fibres based on secondary raw materials; recycling; concrete